@ the crossroads of advocacy and grammar: teaching neopronouns in the German language classroom - White, Jamey Alan (Kansas State University, 2024)
Language and gender as social constructs are in flux and come into intersection in the language classroom. When language teachers go about discussing the notions of gender and grammatical gender, if they are not careful, their words can contribute to the reification and perpetuation of the violent and exclusionary designs from the past. Instead of ignoring or avoiding opportunities to discuss structural and systemic erasure of people who are gender non-conforming, there is an imperative for teachers to do the opposite: demonstrate the flexibility of language for their students to include those who do not fit into the gender binary, illustrate how language can empower people to develop their identities and opinions, and showcase the differences and similarities between the cultures in which those languages are spoken. This is because the goals of the foreign language classroom must be oriented around students’ abilities to express themselves authentically and should foster their development of appropriate and respectful behavior when communicating with others in a constantly changing world. This paper surveys current discourses on gender and grammatical gender and suggests a possible framework for use of gender non-specific language, especially pronouns, in the foreign language classroom.
At the crossroads of advocacy and grammar: teaching neopronouns in the German language classroom
Keywords: Neopronouns; German; Teaching; Gender identity; Gender non-specific language; Foreign language classroom